1993
DOI: 10.1107/s0108270192012216
|View full text |Cite
|
Sign up to set email alerts
|

A twist-boat 1,3,5-triaryl-1,3,5-triazacyclohexane: X-ray analysis of the inclusion compound formed between 1,3,5-tris(p-nitrophenyl)-1,3,5-triazacyclohexane and pyridine

Abstract: The triazacyclohexane ring adopts a twist-boat conformation with torsion angles -25.3 (2), -41.3 (2), 70.3 (2), -27.7 (2), -35.8 (2) and 66.0 (2) °. The N--C(aryl) bonds from the ring have lengths of 1.356 (3), 1.382 (3) and 1.400 (3) ,4, and are inclined at 3.3(2), 21.2(2) and 29.5 (3) ° to the CH2--N--CH2 planes. The N--C bond lengths in the triazacyclohexane ring are 1.442 (3)-1.474 (3)A. The pyridine molecules are accommodated in an ordered manner in channels aligned along the screw axes parallel to b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The puckering parameters (Cremer & Pople, 1975), ' = À15 (5) and = 3.1 (2) , agree perfectly with a chair conformation. As reported by Gilardi et al (2003), such a chair conformation is observed in most of the 1,3,5-triazacyclohexanes reported to date with the exception of 1,3,5-tris(pnitrophenyl)-1,3,5-triazacyclohexane (Adam et al, 1993), which has a twist-boat conformation.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The puckering parameters (Cremer & Pople, 1975), ' = À15 (5) and = 3.1 (2) , agree perfectly with a chair conformation. As reported by Gilardi et al (2003), such a chair conformation is observed in most of the 1,3,5-triazacyclohexanes reported to date with the exception of 1,3,5-tris(pnitrophenyl)-1,3,5-triazacyclohexane (Adam et al, 1993), which has a twist-boat conformation.…”
supporting
confidence: 60%
“…X-ray crystallographic investigations of 1,3,5-trialkyl and 1,3,5-triaryl derivatives of 1,3,5-triazacyclohexane have mainly shown the expected chair conformation with a pyramidal arrangement of bonds at the N atoms (Wellington et al, 1885;Bouchemma et al, 1988Bouchemma et al, , 1990Adam et al, 1993Adam et al, , 1995Gilardi et al, 2003;Latreche et al, 2006a). In the present study, a new compound, (I), containing trizacyclohexane is reported.…”
mentioning
confidence: 58%
“…For the conformations of 1,3,5-triaryl derivatives of 1,3,5-triazacyclohexane, see: Wellington & Tollens (1885); Bouchemma et al (1988); Adam et al (1993); Gilardi et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…There are 33 similar compounds in the Cambridge Structural Database (CSD, Version 5.24; Allen, 2002), all containing the 1,3,5-triazacyclohexane ring with different substituents on the N atoms. 32 of these compounds have chair conformations, the exception being 1,3,5-tris(p-nitrophenyl)-1,3,5-triazacyclohexane (Adam et al, 1993), which has a twist-boat conformation.…”
Section: Commentmentioning
confidence: 99%